Sobrevivência constante ou variada? implicações de fatores sazonais e imprevisíveis na sobrevivência em um passeriforme de ambiente neotropical semiárido - Oliveira, Carlos Allan de Souza (Universidade Federal Rural do Semi-Árido, 2019)
Dry neotropics are seasonal and partly unpredictable environments regarding the occurrence and volume of intra and inter yearly rains, being this climatic feature determining in the patterns of survival and energetic allocation in routines of the yearly cycle (reproduction and flight-feathers molt in Passeriformes. We used data of capture-marking-recapture of the Pearly-Vented-Tody-Tyrant (Hemitriccus margaritaceiventer) in order to test the hypothesis that the levels of precipitation intra and inter yearly, reproduction and flight-feathers molt would influence the rating of apparent survival. Our hypothesis indicate that periods of higher precipitation determine elevated ratins of survival if compared to periods of drought. Moreover, reproduction and flight-feathers molt are associated to survival through trade-off, and therefore survival estimates should decline during these activities. We realized sampling for six years each fourteen or twenty-eight days in a forest seasonally dry of Brazilian Northeast, inserted in a vegetal formation known as Caatinga. We used the Cormack-Jolly-Seber (CJS) formulation for building the demographic models and estimate the probabilities of survival and recapture of the birds. The analysis of the average of the models as supporter to explain the data variation indicated not exist variation intra and inter yearly in the apparent survival ratings (between 0.91 and 0.97) independent of the season annual, rainfall period or brood patch and moult occurrence The apparent survival of the specie remained high and constant throughout the study, and our evidence indicates that these results are explained by physiological and behavioral adjustments to tolerate climatic variations such as the occurrence of energetically costly activities in periods of favorable environmental conditions, reduction of fertility rates, and increased displacement during droughts
Keywords: Caatinga; Cormack-Jolly-Seber; Chuvas; Hemitriccus margaritaceiventer; História de vida; Caatinga; Cormack-Jolly-Seber; Rain; Hemitriccus margaritaceiventer; Life history; CIENCIAS BIOLOGICAS::ECOLOGIA